Synthesis and characterization of natural lanthanum labelled DOTA-Peptides for simulating radioactive Ac-225 labeling - Ucar, Burcu (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
This research aimed to assess the labeling procedure of Lanthanum to DOTATATE and PSMA-617 peptide for simulating Actinium-225 (Ac-225) labeling. For this purpose labeling procedure, purification and characterization conditions were optimized. Results showed that for the high reaction yield labeling, microwave heating should be preferred and Sephadex G10 column was found to be more suitable as a purification system compared to Toyopearl column. For the characterization of complex, more precise and reliable results were obtained by the chromatographic system.
Keywords: Lanthanum (III) chloride; Peptide labeling; Ac-225; DOTATATE; PSMA-617; SOMATOSTATIN; COMPLEXES; Chemistry; Nuclear Science & Technology; Radiology, Nuclear Medicine & Medical Imaging